The The Relationship between Functional Status and Depression among Elderly at Himo-Himo Nursing Home Ternate 2024 - Al Jihad, Adam Thariq; Hidayat, Ferdian; Pontoh, Lely Maryanti (Surabaya Physical Medicine and Rehabilitation Journal, 2026)
Background: The elderly population in Indonesia is approximately 15.16 million people. The elderly experience an aging process that tends to decrease functional capacity, both at the cellular level and the organ level, in line with the aging process. The decline in functional ability in the elderly is associated with depression. Poor functional status can trigger stress, resulting in poor overall mental health and emphasizing the risk of greater functional decline with increasing age. Aim(s) (including purpose setting): To determine the relationship between functional status and depression among the elderly at the Himo-Himo Nursing Home, Ternate in 2024. Material and methods: This study uses an observational analytic approach with a total sampling technique, and data collection was conducted using the Barthel Index and Geriatric Depression Scale (GDS) questionnaires. Statistical analysis was performed using univariate and bivariate analysis with the Spearman correlation test. Result: There were a total of 38 elderly individuals who participated in this study, with the majority in the older age category (65-75 years) (63.2%), female (52.6%), and a residence duration in the nursing home of more than 36 months (65.8%). Mild depression was observed in (47.4%) and moderate depression in (15.8%). Functional status in the independent category was (60.5%). The Spearman correlation test showed a positive correlation (p-value = 0.003, r = 0.471). Conclusions: There is a significant relationship between functional status and depression in the elderly at the Himo-Himo Nursing Home, Ternate City, with a positive correlation.